Persisting Embryonal Infundibular Recess in Morning Glory Syndrome: Clinical Report of a Novel Association - D'Amico, A.; Ugga, L.; Cuocolo, R.; Cirillo, M.; Grandone, A.; Conforti, R. (American Journal of Neuroradiology, 2019)
SUMMARY: Morning glory syndrome is characterized by a congenital optic disc defect that resembles the eponymous flower. We present the MR imaging findings of 2 pediatric patients with morning glory disc anomaly and persisting embryonal infundibular recess, another rare malformative finding, a previously unreported association. Neuroradiologists should be aware of the possible presence of a persisting embryonal infundibular recess in patients with morning glory syndrome, to aid in the differential diagnosis including other pituitary malformations such as pituitary stalk duplication.MGDAmorning glory disc anomalyMGSmorning glory syndromePEIRpersisting embryonal infundibular recess